Defects band enhanced by resonance Raman effect in praseodymium doped CeO2. (25th May 2016) - Westermann, Alexandre; Geantet, Christophe; Vernoux, Philippe; Loridant, Stéphane
Abstract : In this work, the origin of the Raman defects band at 570 cm −1 of praseodymium‐doped ceria was revisited from in situ spectra using six different exciting lines between 458 and 785 nm at low temperatures after oxidizing or reducing treatment. The observation of overtones and the fast change of relative intensity with excitation wavelength were explained by a resonance effect around 514 nm, which involved a Pr 4+ containing defect stabilized at the oxidized state leading to an absorption band around 530 nm. The reduction of Pr 4+ cations contained in such defects modifies the electronic properties of praseodymium doped ceria inhibiting the resonance effect. Additionally, the number of D1 defects that involved Pr 3+ cations and oxygen vacancies increased allowing them to be distinguished. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The origin of the Raman defects band at 570 cm −1 of praseodymium‐doped ceria was revisited from in situ spectra using six different exciting lines between 458 and 785 nm at low temperatures after oxidizing or reducing treatment. The observation of overtones and the fast change of relative intensity with excitation wavelength were explained by a resonance effect around 514 nm, which involved a Pr 4+ containing defect stabilized at the oxidized state.